Kontaminasi Sel Darah Merah dengan Sisa Bahan Anestesi dalam Cartridge Pasca Injeksi Anestesi Lokal - Budiono Budiono; Bagas Luthfi Alfat; Hayyu Failasufa; Septi Duvasti; Vilianti Eka Fitri Rahatina (Universitas Muhammadiyah Semarang, 2022)
Background: The use of residual anesthetic solution for other patients is still carried out by several dentists. Blood in the veins can provide back pressure after deponir anesthetic fluid so that the cartridge can be contaminated with blood as a result of the back pressure. Blood that has been infected by a pathogen can be the easiest way to transmit a disease. The purpose of this study was to determine the presence of red blood cell contamination in the remaining anesthetic in the cartridge after injection of local anesthetic using an S brand intraigamentary syringe. Method: An analytical observational study with a cross sectional design. Using accidental sampling technique with a total of 20 samples. The material used is a cartridge containing 3% mepivacaine hydrochloride. Researchers used cartridges after anesthesia procedures to patients, then observations were made using Urinalysis Reagent Strips (Urine). Test data analysis using point-biserial correlation. Result: It was found that 14 samples had red blood cell contamination (65%) and 7 samples did not have red blood cell contamination (35%). There was a close relationship between red blood cell contamination of the remaining anesthetic solution in the cartridge (r = - 0.864) and there was a significant relationship between red blood cell contamination and the remaining anesthetic solution in the cartridge with a P value of 0.000 (P < 0.01). Conclusion: There is contamination of red blood cells in the remaining anesthetic solution in the cartridge using an S brand intraigamentary syringe.